2016
DOI: 10.1017/s0007485315001121
|View full text |Cite
|
Sign up to set email alerts
|

The life cycle ofGregarina cuneatain the midgut ofTribolium castaneumand the effects of parasitism on the development of insects

Abstract: Tribolium castaneum Herbst 1797 (Coleoptera: Tenebrionidae), an important pest of stored grains and byproducts, is naturally infected by Gregarina cuneata Stein 1848 (Apicomplexa: Gregarinidae). Changes in the life cycle of insects caused by the parasite development in the midgut were studied. Trophozoites, gamonts (solitary and associated), and gametocysts were present in the midgut of the insects. In young trophozoites, the apical region differentiated into an epimerite that firmly attached the parasite to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Likewise, a gregarine prevalence of 91% was found in field‐collected beetles of Tribolium castaneum (Tate & Graham, ). In this beetle, gregarine infection can drastically increase mortality, likely due to the nutrient depletion caused by the parasite (Gigliolli et al., ). In Phaedon brassicae populations, infection rates of 100% were found (Kim, Min, Kwon, Choi, & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a gregarine prevalence of 91% was found in field‐collected beetles of Tribolium castaneum (Tate & Graham, ). In this beetle, gregarine infection can drastically increase mortality, likely due to the nutrient depletion caused by the parasite (Gigliolli et al., ). In Phaedon brassicae populations, infection rates of 100% were found (Kim, Min, Kwon, Choi, & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…The insect's ability to utilize plant nutrients and to detoxify allelochemicals may be enhanced or diminished by symbiotic or parasitic microorganisms occurring in the gut (Engel & Moran, ; Welte et al., ). Gut microbiota may assist in digesting and supplementing a low‐quality diet (Scully et al., ) but could also have detrimental effects caused by nutrient depletion (Gigliolli, Julio, & Conte, ). Moreover, the composition of gut microbiota affects the immune responses of herbivores (Tate & Graham, ).…”
Section: Introductionmentioning
confidence: 99%
“…They can lead to a delayed development, higher mortality, and reduced reproduction of their hosts (Zuk 1987a ; Córdoba-Aguilar et al 2003 ). Nutrient deprivation induced by the gregarines may be causing some of these negative effects (Gigliolli et al 2016 ). However, gregarine infections can also be benign for their hosts (Harry 1967 ; Kim et al 2014 ) or even beneficial, for example, by accelerating the development or lowering predation (Alarcón et al 2017 ; Soghigian et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, a large number of studies showed that the presence of gregarines typically comes with a broad range of costs for the hosts. For instance, gregarine infection reduces body weight and food consumption in the grasshopper Atractomorpha crenula (Johny et al, 2000), increases susceptibility to a fungal pathogen in the cockroach Blattella germanica (Lopes and Alves, 2005) and hampers larval and pupal development in the mosquito Aedes triseriatus (Beier, 1983) and the red flour beetle Tribolium castaneum (Gigliolli et al, 2016). In several damselfly species, the presence of gregarines also alters survival, egg production, mating decisions, oviposition strategies and wing ornaments (Córdoba-Aguilar et al, 2003;Córdoba-Aguilar and Munguía-Steyer, 2013;Suhonen et al, 2017), while it reduces the capability of male odonates to defend their territory (Siva-Jothy and Plaistow, 1999).…”
Section: Introductionmentioning
confidence: 99%